A family secret - Heuvel, Eric, 1960-; Miller, Lorraine T. (New York : Farrar, Straus, Giroux, 2009)
While searching his Dutch grandmother's attic for yard sale items, Jeroen finds a scrapbook which leads Gran to tell of her experiences as a girl living in Amsterdam during the Holocaust, when her father was a Nazi sympathizer and Esther, her Jewish best friend, disappeared.
A Junior Library Guild selection
"Anne Frank House in cooperation with the Resistance Museum of Friesland."
Keywords: Holocaust, Jewish (1939-1945) -- Comic books, strips, etc; Holocaust survivors -- Comic books, strips, etc; Jews -- Netherlands -- Comic books, strips, etc; Nazis -- Comic books, strips, etc; Grandmothers -- Comic books, strips, etc; Holocaust, Jewish (1939-1945) -- Fiction; Holocaust survivors -- Fiction; Jews -- Netherlands -- Fiction; Nazis -- Fiction; Grandmothers -- Fiction; Graphic novels; Graphic novels